2013
DOI: 10.1074/jbc.m113.471904
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Contextual Discrimination Involves the Appearance of a RAS-GRF1/p38 Mitogen-activated Protein (MAP) Kinase-mediated Signaling Pathway That Promotes Long Term Potentiation (LTP)

Abstract: Background:The ability to distinguish similar experiences is a critical aspect of memory. Results: Contextual discrimination involves LTP promoted by calcium-permeable AMPA-type glutamate receptors, RAS-GRF1 and p38 MAP kinase. Conclusion: A newly discovered, LTP-supporting, signaling pathway contributes to a key component of memory formation. Significance: Defects in this signaling pathway may contribute to cognitive loss associated with neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 49 publications
1
47
1
Order By: Relevance
“…Expression of this form of AMPARs in the hippocampus enhances LTP (Jia et al 1996;Wiltgen et al 2010;Sanderson et al 2012;Jin et al 2013), which utilizes a distinct pathway compared with a traditional NMDARdependent LTP (Jia et al 1996;Wiltgen et al 2010;Jin et al 2013;Kim et al 2015a). In this study, we reveal that KO animals show enhanced hippocampus-dependent contextual fear learning and memory (Fig.…”
Section: +mentioning
confidence: 57%
See 2 more Smart Citations
“…Expression of this form of AMPARs in the hippocampus enhances LTP (Jia et al 1996;Wiltgen et al 2010;Sanderson et al 2012;Jin et al 2013), which utilizes a distinct pathway compared with a traditional NMDARdependent LTP (Jia et al 1996;Wiltgen et al 2010;Jin et al 2013;Kim et al 2015a). In this study, we reveal that KO animals show enhanced hippocampus-dependent contextual fear learning and memory (Fig.…”
Section: +mentioning
confidence: 57%
“…A previous study shows that CP-AMPAR expression in the hippocampus is required for contextual discrimination (Jin et al 2013), thus CP-AMPAR expression in the KO hippocampus could increase contextual discrimination, leading to enhanced fear learning. Since GluA1-pS845 levels are lower in the KO amygdala (Fig.…”
Section: +mentioning
confidence: 94%
See 1 more Smart Citation
“…Previous characterization of GRF1-knockout (KO) mice has documented a specific implication of this protein in memory formation (Brambilla et al, 1997;Giese et al, 2001), postnatal growth (Itier et al, 1998;Fernández-Medarde et al, 2002), pancreatic β-cell function and glucose homeostasis (Font de Mora et al, 2003;Manyes et al, 2014), and neurosensory processes and photoreception (Fernández-Medarde et al, 2007Hysi et al, 2010). By contrast, the study of Rasgrf2-null animals has demonstrated that GRF2 and GRF1 are not functionally overlapping regarding memory formation or body growth (Fernández-Medarde et al, 2002;Jin et al, 2013;Li et al, 2006) and has also documented that GRF2 plays specific functional roles in control of T-cell proliferation and signaling in lymphocyte proliferation, T-cell signaling responses and lymphomagenesis (Ruiz et al, 2007(Ruiz et al, , 2009. Recent studies of specifically affected human patient subpopulations support a role of GRF1 in predisposition to myopia and refractive errors of vision (Hysi et al, 2010) and of GRF2 in predisposition to addictive alcohol abuse (Easton et al, 2014;Schumann et al, 2011;Stacey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that RasGRF1 contributes to contextual discrimination by regulating a specific form of postsynaptic plasticity called high frequency long-term potentiation (HFS-LTP, (Jin et al, 2013) in the CA1 region of the hippocampus. Additionally, this signaling was dependent on p38 activation.…”
Section: Introductionmentioning
confidence: 99%